Carbon quantum dots: A promising nanocarrier for bioimaging and drug delivery in cancer. (August 2022) - Jana, Pradip; Dev, Abhimanyu
Abstract: Recently, carbon quantum dots have emerged as a promising nanomaterial for simultaneous bioimaging and drug delivery in cancer due to their excellent properties like fluorescence emission, good photostability, high water solubility, good biocompatibility, small size, ease in surface functionalization and low toxicity. The current review discusses the different synthetic routes, post synthesis modifications, optical properties and characterization techniques for carbon dots. Further, problems associated with cancer chemotherapy and the potential nanomaterial-based strategies to overcome it, have been highlighted. Besides, the recent progress in the domain of carbon dots-based strategies in anticancer drug delivery and real time monitoring through fluorescence imaging are also discussed. In continuation, approaches like carbon dots based active and passive targeting, tumor microenvironment targeting, multifunctional targeting, etc. are elaborated. Carbon dots applications for in vivo imaging and biodistributions in cancer models are also collectively presented. Finally, critical opinions and future scopes in the development of carbon dots based advanced nano-theranostics in cancer treatment are discussed. The current review can offer broader vision and a sound roadmap to the researchers working in the domain of cancer nano-theranostics and cancer targeted drug delivery. Graphical Abstract: ga1